The importance of pharmaceutical care in the release of drugs for the prevention and treatment of acne in women - Оlena Temirova; Julia Krat; Mykola Khaitovych (Bogomolets National Medical University, 2022)
acne vulgaris ranks third in the structure of dermatological diseases and is an urgent medical and social problem. The disease is often the cause of psycho-emotional disorders and contributes to the deterioration of patients' quality of life and social activity. However, the treatment of acne vulgaris is complex and long-term. This study aims to assess the role of pharmaceutical care in the release of drugs to prevent and treat acne in women. An anonymous survey of 100 teenage girls and women of different ages on a single specially designed questionnaire, considering the problems of acne treatment. Methods of an anonymous questionnaire survey, computer data processing, and graphics are used. It was found that the majority (82 %) of respondents considered the treatment of acne vulgaris to be problematic. In addition, only 36 % of respondents sought medical help, while the majority resorted to self-medication. The main drugs of choice were salicylic (42 %) and azelaic acids (38 %), clindamycin (24 %), benzoyl peroxide (11 %), and isotretinoin (10 %). In most cases (58 %) complex therapy was used. In addition, almost 60 % of respondents used sorbents during the treatment of acne vulgaris, and almost 20 % - combined oral contraceptives. Most respondents reported improvement after the end of treatment (57 %) and at least a week of therapy (29 %). It is important to note that 38 % of respondents noted the occurrence of adverse side effects with anti-acne drugs, the most common of which were: dry skin (68.7%), redness (56.3 %), increased rash (25.0 %), and itching (20.8 %). In addition, most respondents (80 %) did not observe facial hygiene and tried to "squeeze" acne vulgaris. At the same time, only half of the respondents received recommendations on the regime and rules for the use of anti-acne drugs from pharmacists. While within the framework of pharmaceutical care, pharmacists identify threatening conditions that require medical attention, provide recommendations on the rules and mode of use of over-the-counter drugs, and carry out informational and educational work on facial hygiene, dietary modifications, and non-drug measures. Therefore, given the high prevalence of self-medication, the use of several drugs, the importance of following the rules of skin hygiene, and providing quality pharmaceutical care are necessary for achieving the most effective and safe treatment of acne.